Preoperative vascular surgery model using a single polymer tough hydrogel with controllable elastic moduli. Issue 34 (13th August 2020) - Ballance, William C.; Karthikeyan, Vignesh; Oh, Inkyu; Qin, Ellen C.; Seo, Yongbeom; Spearman-White, Tremaan; Bashir, Rashid; Hu, Yuhang; Phillips, Heidi; Kong, Hyunjoon
Abstract : Polyacrylamide hydrogel composition can be tuned to result in tough, soft, and sutureable vascular models. Abstract : Materials used in organ mimics for medial simulation and education require tissue-like softness, toughness, and hydration to give clinicians and students accurate tactile feedback. However, there is a lack of materials that satisfy these requirements. Herein, we demonstrate that a stretchable and tough polyacrylamide hydrogel is useful to build organ mimics that match softness, crack growth resistance, and interstitial water of real organs. Varying the acrylamide concentration between 29 or 62% w/w with a molar ratio between cross-linker and acrylamide of 1 : 10 800 resulted in a fracture energy around ∼2000 J m −2 . More interestingly, this tough gel permitted variation of the elastic modulus from 8 to 62 kPa, which matches the softness of brain to vascular and muscle tissue. According to the rheological frequency sweep, the tough polyacrylamide hydrogels had a greatly decreased number of flow units, indicating that when deformed, stress was dispersed over a greater area. We propose that such molecular dissipation results from the increased number of entangled polymers between distant covalent cross-links. The gel was able to undergo various manipulations including stretching, puncture, delivery through a syringe tip, and suturing, thus enabling the use of the gel as a blood vessel model for microsurgery simulation.